2007
DOI: 10.1117/12.733685
|View full text |Cite
|
Sign up to set email alerts
|

EUV lasers on low-inductive capillary discharges

Abstract: Results of experimental and numerical researches of problems, connected with creation of compact EUV lasers with a close geometry of electrodischarge systems, with long transporting lines for its energy supply and preliminary gas preionization by running wave of avalanche sliding discharge are reported. Both pumping schemes with collision excitation on example of neon-like ions of argon and collision recombination on example of hydrogen-like ions of nitrogen are considered. The input energy balance and questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This appeared to restrain researchers' efforts to increase the energy parameters of non-chain HF (DF) lasers. Although there have been numerous works concerned with non-chain HF (DF) lasers, the radiation energy attained for them by 1996 was at the level of 10 J [16][17][18]. The incompleteness of the traditional understanding of the physics of forming SSVD in dense gases came to be understood after we found that it was possible to obtain discharge in SF 6 and mixtures of SF 6 with hydrocarbons (deuteron-carbons) in the systems of plane electrodes with high electric field enhancement at the edge without any preionization in a gas [2,3].…”
Section: A New Form Of Ssvdmentioning
confidence: 99%
See 1 more Smart Citation
“…This appeared to restrain researchers' efforts to increase the energy parameters of non-chain HF (DF) lasers. Although there have been numerous works concerned with non-chain HF (DF) lasers, the radiation energy attained for them by 1996 was at the level of 10 J [16][17][18]. The incompleteness of the traditional understanding of the physics of forming SSVD in dense gases came to be understood after we found that it was possible to obtain discharge in SF 6 and mixtures of SF 6 with hydrocarbons (deuteron-carbons) in the systems of plane electrodes with high electric field enhancement at the edge without any preionization in a gas [2,3].…”
Section: A New Form Of Ssvdmentioning
confidence: 99%
“…It should also be mentioned that analysis of the literature data indicates a negligible role for preionization in the formation of SSVD in non-chain lasers. For example, in [16], where a set of metal rods connected to a common busbar through a resistance (resistance uncoupling) served as the discharge gap cathode, preionization was absent, while in [18] it was performed through a high current dielectric surface discharge whose spectrum displayed not only UV radiation, but also soft x-ray radiation.…”
Section: A New Form Of Ssvdmentioning
confidence: 99%
“…Obtained results were published in the proceedings of international conferences [3][4][5][6][7][8] and papers in scientific journals [9][10][11][12][13][14]. In this work, we report new still unpublished data that are important for understanding the entire set of topical issues and for analyzing, in view of present-day concepts, the relevance of such investigations.…”
Section: Introductionmentioning
confidence: 97%